Focussing on the message New Testament hermeneutics, exegesis and methods, Andrie Du Toit (Ed.) - Kok, Jacobus (Neotestamentica, 2010)
This book represents one of the most comprehensive introductions to current theoretical approaches to the exegesis and interpretation of the NT I have come across in recent years. I can recommend it unconditionally as a standard methodological introduction to students of the NT. Furthermore, the specialized scholars who contributed to the book all made their mark in the world of Biblical studies, for instance the renowned Prof. Dr. Andrie Du Toit, (editor) who until recently served as president of the prestigious Societas Novi Testamenti Studiorum (2008-2009) and others like Bernard Lategan, Jan van der Watt, Andries Van Aarde, etc. On a general epistemological level, the book's approach reflects the methodological shift that has taken place in recent years in which the focus shifted from the origins and prehistory of the text (world behind the text) to the world in and in front of the text and the hermeneutical dimension thereof, i.e. presenting methods functioning on the synchronic level. In this new methodological approach we find a stronger inter-disciplinary approach to biblical exegesis in which the insights of communication science, linguistics, literary and social studies, modern rhetoric, etc. contribute to the better understanding of biblical texts. I am of the opinion that the scholars in this book succeeded in retaining the positive aspects of traditional exegetical approaches, but also successfully adopted, tested and adapted valuable input from other disciplines with methodological clarity and thoroughness (all in more than 600 pages).